Enhancing Customer Experience through Business Intelligence: Preference and Behavior - Alsaaideh, Majdi; Kilani, Yanal (International Review of Management and Marketing, 2026)
The current study aimed to explore the influence of business intelligence (BI) in terms of (personalization, predictive analytics, segmentation, feedback analysis and Omni-channel integration) in enhancing customer experience (CE) in terms of preferences and behavior. A convenient sample of (237) employees responded to a self-administrated questionnaire and SPSS was used to deal with collected primary data. Results of analysis indicated that BI is able to influence CE in terms of preferences and behavior from perspective of senior employees of electronics trading organizations operating in Jordan. Among the chosen variables of BI characteristics, we have notices that Omni-channel integration scored the highest influence among all adopted variables with a strong correlation that accounted for 86.1% of the variations in the measurements we make. Study recommended that organizations must focus on the efficient connection of multiple channels to provide coherent and pleasurable customer experiences. Further recommendations were presented in the study.